Direct Synthetic Routes of MXenes and Their Application in Carbon Fiber Reinforced Plastics (CFRPs) As Supplementary Sizing Layer† - Dev Patel; Meetkumar Joshi; Yashraj Pranavbhai Joshi; Indra Neel Pulidindi; Suresh Selvaraj (International Journal of Crystalline Materials, 2024)
Sized carbon fibers with a supplementary sizing layer of MXenes (synthesized via traditional MAX phases), bonded to carbon fibers (CFs) as well as the resin matrix via different kinds of physicochemical (van der Waals force, hydrogen bonding, covalent bonding) interactions enhanced the performance of the resulting carbon fiber reinforced plastic (CFRP) materials. This is because of the strong interface generated due to the appearance of MXene at the interface of the CF and the resin matrix. Excellent enhancement in the interfacial and mechanical properties of the CFRPs with MXene modified interfaces were highlighted. Use of new two dimensional (2D) layered crystalline MXene phases and morphologies, that were made possible with the advent of the new synthetic strategies (solid state as well as chemical vapour deposition) excluding the use of MAX phases, need to be exploited for forming the supplementary sizing layer over the CFs for a breakthrough in the CFRP technology, The supplementary sizing layer of MXenes not only strengthens the bond between the CFs and the matrix but also contributes to improved durability and mechanical properties. The unique properties of MXenes, including their high electrical conductivity and chemical stability, further amplify the functionality of CFRPs. Future research should focus on exploring novel MXene phases and morphologies, synthesized via innovative methods like solid-state techniques and chemical vapor deposition, to optimize the interfacial properties and achieve unprecedented performance in CFRPs. This approach holds promise for the next generation of high-performance composite materials, pushing the boundaries of current CFRP technology.
Keywords: CFRPs; Carbon fibers; MXenes; carbon fiber reinforced plastics; sizing layer; transition metal carbides/nitrides/carbonitrides